Immunoregulatory Effects of Codonopsis pilosula Polysaccharide Modified Selenium Nanoparticles on H22 Tumor-Bearing Mice - Yan Long; Hongfei Ji; Jiajing Yang; Haiyu Ji; Keyao Dai; Wenjie Ding; Guoqiang Zheng; Juan Yu (Foods)
Codonopsis pilosula polysaccharide (CPP) and rare element selenium (Se) have been proved to exert various biological activities, and our previous study demonstrated that selenium nanoparticles modified with CPP (CPP-SeNPs) possessed significantly enhanced tumor cytotoxicity in vitro. This study aimed to investigated the inhibitory effects of CPP-SeNPs complex on H22 solid tumors via immune enhancement. In this study, the H22 tumor-bearing mice model was constructed, and the potential mechanisms of CPP-SeNPs antitumor effects were further explored by evaluating cytokines expression levels, immune cells activities and tumor cells apoptotic indicators in each group. The results demonstrated that CPP-SeNPs effectively exerted dose-dependent protective effects on the immune organs of tumor-bearing mice in vivo, leading to increase in peripheral white blood cell counts and inhibition of solid tumor growth with inhibitory rate of 47.18% in high-dose group (1.5 mg/kg). Furthermore, CPP-SeNPs treatment significantly elevated the levels of TNF-α, IFN-γ, and IL-2 in mice sera, enhanced NK cell cytotoxicity, augmented macrophage phagocytosis capacity, as well as increased both the amounts and proliferation activity of lymphocyte subsets. CPP-SeNPs improved the immune system’s ability to clear tumor cells by up-regulating Bax expression while down-regulating Bcl-2 expression within solid tumors, indicating the potential activation of mitochondrial apoptosis pathway. Therefore, CPP-SeNPs administration can effectively inhibit tumor growth by enhancing immune response in tumor-bearing mice, which might be relevant to the regulation of gut microbiota short-chain fatty acids metabolisms. These findings could provide theoretical support and data foundation for further development of CPP-SeNPs as functional food and drug adjuvants.